Experimental investigation of intensification of the process of dissolved-air flotation in wastewater treatment of milk processing enterprises - Шевченко, Тамара Александровна; Шевченко, Андрей Александрович (Eastern-European Journal of Enterprise Technologies, 2016)
Intensification of operation of the flotation plant for wastewater treatment of dairy enterprises by applying a specially designed mixing insert (diaphragm) in the reactant treatment system is investigated. The optimum parameters of the flotation plant to achieve the required quality of wastewater treatment of dairy enterprises for discharge into the city sewer system are determined. It is found that when applying the aluminum sulfate Al2(SO4)3 coagulant, its dose is lower than that of the ferric chloride FeCl3 coagulant by 37.7-38.8 %, and the wastewater treatment efficiency on a laboratory flotation plant, which uses an improved design of the mixing insert (diaphragm) is approximately equal in both cases. Virtual models of the flow in a mixing device with the diaphragm of special design installed therein, which demonstrate and simulate the velocity diagrams in the cross section of the mixing device and flow turbulence are obtained. Major influence factors of wastewater of milk processing enterprises, including pollutant concentrations, coagulant doses and flow rate in the mixing device are given.